2016
DOI: 10.1111/jcpt.12491
|View full text |Cite
|
Sign up to set email alerts
|

Exploring New Zealand prescription data using sequence symmetry analyses for predicting adverse drug reactions

Abstract: New Zealand prescription database can be a potential source to identify ADRs engaging the PSSA method, and this could complement pharmacovigilance surveillance in NZ. The PSSA can be an important method for post-marketing surveillance and monitoring of ADRs which have relatively short latency. However, the predictive validity of PSSA will be compromised in certain scenarios, particularly when sample size is small, when new drugs are in the market and data are sparse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…As expected, we found that older adult loop diuretic initiators were over 8 times more likely to receive potassium supplementation simultaneously or after, rather than before, loop diuretic initiation, consistent with a high incidence of the “loop diuretic‐hypokalemia‐potassium supplementation” prescribing cascade. In sensitivity analyses excluding those who initiated loop diuretics and potassium supplementation on the same day, we obtained qualitatively similar results, as well as findings consistent with a previous PSSA conducted in New Zealand, which showed the new use of furosemide was associated with subsequent potassium supplementation initiation (aSR 2.9, 95% CI 2.8–3.1) 50 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As expected, we found that older adult loop diuretic initiators were over 8 times more likely to receive potassium supplementation simultaneously or after, rather than before, loop diuretic initiation, consistent with a high incidence of the “loop diuretic‐hypokalemia‐potassium supplementation” prescribing cascade. In sensitivity analyses excluding those who initiated loop diuretics and potassium supplementation on the same day, we obtained qualitatively similar results, as well as findings consistent with a previous PSSA conducted in New Zealand, which showed the new use of furosemide was associated with subsequent potassium supplementation initiation (aSR 2.9, 95% CI 2.8–3.1) 50 …”
Section: Discussionsupporting
confidence: 86%
“…In sensitivity analyses excluding those who initiated loop diuretics and potassium supplementation on the same day, we obtained qualitatively similar results, as well as findings consistent with a previous PSSA conducted in New Zealand, which showed the new use of furosemide was associated with subsequent potassium supplementation initiation (aSR 2.9, 95% CI 2.8-3.1). 50 More surprisingly, our findings suggested that as many as 1 in 3 loop diuretic initiators undergoing this prescribing cascade continued potassium supplementation during the 150-day follow-up, and the daily probability of the relic was the highest approximately 90 days after potassium supplementation initiation. Even considering a more conservative definition of the relic (>30 cumulative days of potassium supplementation after loop diuretic discontinuation), the relic occurred in up to 7.2% of patients, and 14.1% of patients refilled their potassium supplementation again after the estimated date of loop diuretic discontinuation.…”
Section: Discussionmentioning
confidence: 60%
“…Most studies ( n = 88) were retrospective cohort studies, 5 , 7 , 18 , 21 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , …”
Section: Resultsunclassified
“…The most commonly identified prescribing cascades are summarised in Table 2 . These include; amiodarone associated with subsequent thyroid hormone prescriptions for hypothyroidism ( n = 5), 54 , 61 , 79 , 85 , 87 CCBs associated with diuretic prescriptions to treat peripheral oedema ( n = 5), 5 , 7 , 87 , 104 , 105 topical antifungals to treat oral candidiasis following inhaled corticosteroids ( n = 4), 39 , 54 , 56 , 71 anti‐Parkinson medication to treat Parkinsonian symptoms following antipsychotic initiation ( n = 4), 19 , 29 , 100 , 119 urinary anticholinergics to treat urinary incontinence following acetylcholinesterase inhibitors( n = 4), 24 , 26 , 44 , 53 and antitussives to treat cough following angiotensin‐converting enzyme inhibitors (ACEIs) ( n = 3). 18 , 73 , 87 Additional prescribing cascades identified included metoclopramide to anti‐Parkinson medication ( n = 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation